Craniopharyngioma and Metabolic Syndrome: A 5-Year Follow-Up Single-Center Experience - Scarano, Elisabetta; Solari, Domenico; Riccio, Enrico; Arianna, Rossana; Somma, Teresa; Cavallo, Luigi Maria; Romano, Fiammetta; Colao, Annamaria; Di Somma, Carolina (Frontiers in Neurology, 2022)
Patients with craniopharyngioma often have comorbidities, such as obesity and hypopituitarism. These two conditions affect each other and worsen the quality of life of patients, leading to a higher risk of morbidity and mortality. In addition, abdominal obesity, measured as waist circumference (WC), is, together with other parameters (arterial hypertension, hyperglycaemia, hypertriglyceridemia and reduced levels of HDL-cholesterol (HDL)), one of the components of metabolic syndrome (MS). Each one of these morbidities occurs in patients with craniopharyngioma more frequently than in the remaining population. On these bases, we evaluated metabolic parameters in patients with craniopharyngioma at time of diagnosis and after a five-years follow up, comparing these data with those of age-, gender-, WC- and body mass index (BMI)-matched controls. In addition, we evaluated the prevalence of MS according to IDF (MS-IDF) and ATP III (MS-ATPIII) criteria in patients and controls at baseline and after five years. We recruited 20 patients with craniopharyngioma (age 38.5±15 years, 10 M) and 20 age-, gender-, WC- and BMI-matched controls (age 34.16±13.19 years, 10 M). In all patients and controls we evaluated: anthropometric features (height, weight, body mass index (BMI), WC, hip circumference (HP) and waist/hip ratio (WHR)), systolic (SBP) and diastolic (DBP) blood pressure, lipid profile (total- cholesterol (TC), HDL, LDL-cholesterol (LDL), triglycerides (TG) and blood glucose at baseline and after 5 years. Prevalence of MS, according to IDF and ATPIII criteria, was calculated in the two groups at baseline and after 5 years. According to our results, at baseline, patients with craniopharyngioma had a worse metabolic profile than controls and a higher prevalence of MS. Besides, at a five-year follow-up, patients still had impaired metabolic characteristics and more frequent MS (according to IDF and ATPIII criteria) if compared to controls. These data confirm that MS in patients with craniopharyngioma is unresponsive to life-changing interventions and to common pharmacological approach. Other factors may be involved in the evolution of these conditions so further studies are needed to establish the correct management of these patients.